Enhancing customer loyalty programs: a study case of Telekom Malaysia Kota Bharu / Ahmad Hafiz Che Hashim - Che Hashim, Ahmad Hafiz (2011)
In the world of telecommunication, consumers typically patronize multiple service providers, which leave service providers striving to earn a greater portion of consumer expenditures. The purpose of this paper is to find out the principle issues toward enhancing loyalty programs on customer purchasing behavior. The impact of loyalty programs membership on customer purchase behavior is very important. Focusing on loyal customers is frequently argued to be the single most important driver of organizations’ long-term performance, which can lead to increased sales and customer share, lower costs, and higher prices. Therefore marketing scholars emphasize the influence of relationship marketing as a strategically important tool from which customer loyalty can be secured and, as a result, the achievement of higher competitiveness and enhanced customer satisfaction can be accomplished. Findings require confirmation in Telecommunication Company before they may be considered fully generalisable. The study was carried out on a convenience sample of 200 respondents through the distribution of structured questionnaires to Telekom Malaysia’s existing customers within the area of Kota Bharu. The data were analyzed using SPSS through the frequencies analysis, correlation coefficient analysis and regression analysis. From the analysis, the researcher found that Trust, Customer satisfaction, Brand image and Customer Retention have a significant relationship with the relationship marketing. From the findings, it shows that trust is the critical factor while customer retention is the least important factor. Some conclusions are provided in the research and the researcher also stated several recommendations. It is a great pleasure if Telekom Malaysia’s management is willing to evaluate the suggestions from the respondents and the researcher